The Use of Indigenous Institutions In Developing Potential Equity of Coastal Community (Desa Lampanairi Kecamatan Batauga Kabupaten Buton Selatan) - Wa Ode Arsyiah; Kuflia Muak Hara (Iapa Proceedings Conference, 2018)
Abundant ecotourism potential can be developed through customary institutions capable of empowering the community and as government partners in developing ecotourism potential in the village of Lampuoranri, Bautauga District, South Buton Regency. This study aims to describe indigenous institutions in developing the ecotourism potential of the coastal community of Lampanairi village and obtain information about the factors that influence ecotourism potential in the community in Lamporanri village, Batauga sub-district, South Buton district, such as Pilumuno We'e (Mountain Water Festival), Beach tourism, mountain tourism and many more will be explored for potential tourism objects. This study uses qualitative descriptive analysis, the first stage is based on the mechanism in connecting the facts, data, and information that is available, in the form of words or verbal, from people and behaviors that are meant by the researcher. The second stage detects according to the object under study. The third stage interprets data generated through interviews, records, reports, documentation, etc. to be used for validity of research data. The results showed that utilization of customary institutions in developing ecotourism potential in the coastal communities of Lampanairi village Batauga subdistrict of South Buton district has been done with the maximum although the customary institution in this village has not existed since the bloom from the village of Bola. But the villagers still uphold the local wisdom values that exist in the village, especially concerning the customary rituals of mountain water festivities at Wandoke Springs (Pilumuno We'e). The ritual of Pilumuno We'e is still done until now but unfortunately there has been no government involvement in supporting the ritual activity because the government has not yet known about this ritual and the village and society have not considered that this ritual can be made one of the interesting attractions in the village Lampanairi. It requires openness between the government and the village community so that local wisdom is maintained and become one of the tourism destinations that attract and can bring in foreign exchange if the management is done well. Awareness of Lampanairi villagers to the importance of preserving the forests by running the Pilumuno We'e cultural ritual followed by eating together, it shows that the community, village apparatus, traditional leaders, religious figures, community leaders still maintain the existing cultural values with